Barriers for exiting sex work: an exploration on female sex workers (FSW) in Puducherry, India - P. Swathisha; Sibnath Deb (Springer, 2024)
Abstract Exit is not an easy task for a sex worker. Academic investigations of the reasons and barriers to exit from the sex industry are lacking heavily. Sex work is a stigmatised profession, even though the workers find it difficult to exit the same. The current study attempted to understand the barriers faced by female sex workers in Puducherry, a union territory in the southeast part of India, to exit from sex work. The participants comprise 19 female sex workers (FSW) who work in Puducherry. The data were collected through in-depth interviews. All of the participants had thoughts about quitting. The barriers to exit were identified. The barriers were recognised at the individual, interpersonal (microsystem), and structural (macro system) levels within the framework of Bronfenbrenner's Ecological Systems Theory, which are discussed in detail in the paper. The study also identified a lack of support systems for the targeted population.